AN ARTICLE REORGANIZATION MODEL BASED ON EMOTION IMPLIED IN FORUM ARTICLES - Yang, Shih-Ting; Tsai, Yao-Chang (Malaysian Journal of Computer Science, 2020)
At present, the virtual forums are free and convenient speaking platforms, according to the speaking specifications and through the examination of forum administrators, the forum users can publish various articles easily. However, as the number of users increases, it is difficult for the forum administrators to check them one by one, and return all the articles to be revised. Also, the publishers (article providers) may write violative words unconsciously, so the article writers infringe the forum specifications with the publication, and shall revise the violative articles. Therefore, this paper develops an Article Reorganization Model based on Emotion Implied in Forum Articles including Article Expressed Emotion Determination Module and Publisher’s Article Statement Reorganization Module. The first module deduces the emotion type of articles by analyzing representative events of articles, creating emotion word membership coefficient, analyzing similar statements and analyzing emotion probability and stable value. The second module uses integrated semantic similarity analysis, review score analysis and multiple combined sentences establishment, the article’s statement structure can be reorganized. This paper builds a Web-based system and a real-world case is applied to confirm the feasibility of this methodology. For forum administrators, violative articles can be extracted rapidly from the articles with specific emotions and the violative statements will be reorganized. For article writers, the statements of violative articles can be revised automatically to save the time for revising violative articles.